Living Walden Two : B.F. Skinner's behaviorist utopia and experimental communities - Kuhlmann, Hilke, 1969- (University of Illinois Press, 2005)
Describes one of the most controversial fictional utopias of the twentieth century. This book explores the dynamics of the communities, with an examination of the two surviving Skinnerian communities: Comunidad Los Horcones in Mexico, and Twin Oaks in Virginia.